Estradiol production by the Bidder's organ of the toad Rhinella arenarum (Amphibia, Anura): Seasonal variations in plasma estradiol - Scaia, María Florencia (2013)
In bufonids, the Bidder´s organ (BO), located in the anterior pole of the testis, is sometimes referred to as a rudimentary ovary because of the presence of previtellogenic follicles. In males of Rhinella arenarum it has been demonstrated that some follicles are vitellogenic and also express several steroidogenic enzymes in follicular cells. The purpose of this study is to describe seasonal variations in plasma estradiol (E2) and in aromatase activity of the BO, and to determine the capacity of the BO to synthesize E2 from cholesterol in males of R. arenarum. E2 was determined by radioimmunoassay and aromatase activity was measured by transformation of radioactive substrates into products. Results indicate that plasma E2 reached the highest concentration in April and the lowest one in animals captured in June, showing a progressive increase to the end of the year. Plasma E2 and total activity of aromatase in the BO were significantly lower during the pre‐reproductive season than during the reproductive and post‐reproductive seasons. It was also demonstrated that the BO is able to produce E2 from endogenous substrates throughout the year. No correlation was found between plasma E2 and total BO weight, while there was a significant correlation between plasma E2 and total activity of aromatase, and between plasma E2 and E2 produced in vitro. Taken together, these results demonstrate seasonal variations in plasma E2, in bidderian total activity of aromatase and, that the BO of adult males of R. arenarum is able to produce E2 from endogenous substrates.